2015
DOI: 10.1017/jgc.2014.21
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ Perceptions of School Counselling in Singapore

Abstract: This article reports on a qualitative study that set out to understand stakeholders' perception of the school counselling service in Singapore. Using semistructured interviews, this study explored the perceptions of three main stakeholder groups, namely teachers and counsellors working within the schools and those working in the communities. Altogether, 19 interviews were conducted. Two key theme areas were uncovered. First, the stakeholders observed and expected differing levels of confidentiality for informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Fostering greater collaboration between parents and school counsellors may facilitate students’ behaviour to seek school counsellor’s help. The same sentiment was also observed by Low (2015b) where a collaborative effort between teachers, parents and counsellors creates a positive outlook towards school counselling.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Fostering greater collaboration between parents and school counsellors may facilitate students’ behaviour to seek school counsellor’s help. The same sentiment was also observed by Low (2015b) where a collaborative effort between teachers, parents and counsellors creates a positive outlook towards school counselling.…”
Section: Discussionsupporting
confidence: 69%
“…Lee, 2014). There were also varying opinions on the need to have onsite school counselling (Low, 2015b). Some teachers felt that it was not necessary for the students to see a school counsellor since they were able to manage their problems in the past.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The counsellors in the present study felt that teachers were sometimes roadblocks more than they were collaborators. Studies have shown that teachers’ perceptions of a counsellor’s role influence the overall success of the counselling services (Jackson et al, 2002; Low, 2015). A recent study by Atli (2020) highlights how novice school counsellors have to fight the misconceptions and some prejudices that teachers hold about their role.…”
Section: Discussionmentioning
confidence: 99%
“…To curb this challenge Besley (2002) in Chireshe (2006) advocates for the employment of full-time school peer support groups in schools who should be paid as full-time practitioners so that they can only focus on their work to overcome the shortage of time that is currently being experienced in a majority of schools. This worked well in Singapore and Zimbabwean schools where most of the peer support groups worked as full-time school peer supporters (Low, 2018;Chidarikire, 2017) hence they had more time for the learners.…”
Section: Lack Of Timementioning
confidence: 96%